Expert: Carry out studies on 'toxic' shark 'fins - New Straits Times, V.Shankar Ganesh (2012)
THE Fisheries Department and other relevant authorities should carry out studies to see if shark fin soup could pose a significant health risk for degenerative brain diseases.